2021
DOI: 10.15252/embr.202051813
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate triggered phosphoproteome changes and a PIN2 phosphosite modulating root system architecture

Abstract: Nitrate commands genome‐wide gene expression changes that impact metabolism, physiology, plant growth, and development. In an effort to identify new components involved in nitrate responses in plants, we analyze the Arabidopsis thaliana root phosphoproteome in response to nitrate treatments via liquid chromatography coupled to tandem mass spectrometry. 176 phosphoproteins show significant changes at 5 or 20 min after nitrate treatments. Proteins identified by 5 min include signaling components such as kinases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 134 publications
1
18
1
Order By: Relevance
“…Recently, it was shown that nitrate coordinately stimulates cell elongation and cell proliferation and lateral root development via effects on PIN2-mediated auxin transport ( Vega et al, 2021 ; Ötvös et al, 2021 ). This could be linked to nitrate regulated PIN2 phosphorylation changes that stimulated PIN2 secretion and recycling ( Ötvös et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that nitrate coordinately stimulates cell elongation and cell proliferation and lateral root development via effects on PIN2-mediated auxin transport ( Vega et al, 2021 ; Ötvös et al, 2021 ). This could be linked to nitrate regulated PIN2 phosphorylation changes that stimulated PIN2 secretion and recycling ( Ötvös et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Local auxin distribution is achieved by the distinct localization of PIN proteins, which dynamically change in response to developmental cues, such as nutrient levels of the soil. PIN2, which localizes at the cortex and in epidermal cells, channels auxin flow from the root tip towards the elongation zone, creating the auxin gradient in roots together with other auxin transporting proteins [5,47,48]. Auxin efflux carriers PIN2 is important for modulation of root system architecture in response to different nutrient levels of the soil.…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis thaliana, phosphorus deficiency promotes root hair number and length via suppressing vacuolar degradation of PIN2, thus enhancing root absorption capacity and efficiency [29]. PIN2 also plays key role in regulating primary and lateral root growth in response to nitrate, as nitratetreated pin2 mutants showed longer primary roots and less lateral roots number than wild-type plants [48]. Furthermore, the phosphorylation status of PIN2, which regulates polar plasma membrane localization, is necessary for root system architecture modulation in response to nitrate.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate mediates these functions largely through its impacts on endogenous auxin pathways. Numerous aspects of nitrate transport and signaling interact with auxin biosynthesis, signaling and transport (Vega et al, 2019; 2021; Asim et al, 2020; Otvos et al 2021; Liu and von Wirén, 2022). Multiple studies have identified auxin-related genes as differentially expressed in response to nitrate (Gifford et al, 2008; Vidal et al, 2010; 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Nitrate assimilation and signaling have significant crosstalk with auxin transport and signaling pathways in the control of root development (Vega et al, 2019; Asim et al, 2020; Liu and von Wirén, 2022). For example, nitrate regulates root growth in part by modulating the phosphorylation status of the PIN2 auxin transporter (Otvos et al 2021; Vega et al 2021). Nitrate also induces the expression of the auxin receptor AUXIN SIGNALING F-BOX3 (AFB3) (Vidal et al, 2010; Vidal et al, 2013).…”
Section: Introductionmentioning
confidence: 99%